Restructuring and Reshaping of CsPbX3 Perovskites by Lithium Salts. Issue 30 (9th September 2022) - Dumont, Antoine; Nicholson, Eric; Qiu, Chenyue; Pan, Jinbo; Gariepy, Zachary; Du, Shixuan; Howe, Jane; Singh, Chandra Veer; Lu, Zheng‐Hong
Abstract: Metal halide perovskites have exceptional potential for future generations of light‐emitting diodes and solar cells. Compared to widely used solution‐based syntheses, vapor‐phase deposition (VPD) offers a fabrication route that can be more easily scaled up for commercial production. Cesium lead halides (CsPbX3 ) have shown great color purity, high photoluminescence quantum yield, and better stability than other perovskites. To improve the optoelectronic properties, lithium salts are often used as passivation agents to reduce nonradiative defects. Here, it is reported that VPD CsPbX3 thin films can be dramatically reshaped by a lithium bromide adlayer, a salt that is successfully used to drastically increase the luminescent yield of CsPbBr3 . It is found that continuous CsPbBr3 and CsPbCl3 films restructure themselves into islands whereas CsPbI3 films transform into mixed triangular and rod‐shaped crystals. Based on density functional theory (DFT) studies, it is established that a surface energy change by LiBr adlayer is not the main driver for the perovskite film transformation. Instead, DFT simulations indicate that the LiBr adlayer creates a polar surface forming a strong Van der Waals force attracting water molecules. Abstract : LiBr surface passivation reshapes and restructures CsPbX3 continuous films into an assembly of well‐defined islands, rods, and triangular crystals. Density functional theory simulations show that the polarized LiBr‐terminated perovskite surface forms a strong attractive force for water molecules initiating film microstructure transformation.